LATAR, ALUR, PENOKOHAN, TEMA, AMANAT, DAN SITUASI SOSIAL BUDAYA NOVEL GADIS KRETEK KARYA RATIH KUMALA - Suwardo, Suwardo (Widya Warta, 2016)
The research aimed to describe and explain the setting, plot, characterization, theme, message of Gadis Kretek. Besides, it also tried to search the social-cultural value contained within the novel. This research is descriptive-qualitative in nature. The findings are as follows: (1) The spatial setting is Jakarta, Cirebon, Kudus, Muntilan, Temanggung; while, the temporal setting is some time from pre-independence of Indonesia up to 1970s; then, the social setting is Javanese society of low class, middle, and upper class. (2) The plot is chronologically regressive, quantitatively double, and qualitatively loose. (3) The analysis on characterization using analytic and dramatic techniques showed thatÂ  the main characters of the novel are Soeraja , Idroes Moeria, Soedjagad, Roemasia, Dasiyah (Jeng Yah), Pak Trisno, Lebas, and Tegar. (4) The mayor theme of the literary work is the flashback of cigarette industry, the family secret, and the revelation of Djagad Raja cigarette; meanwhile, the minor theme is (a) No matter how tightly a secret is kept, one day it will be revealed and (b) The victory and success of such an effort needs hard work and perseverance. (5) The message of Gadis Kretek is that the author would like to confirm the readers that honesty, hard work, openness, and education are the priority to struggle in life in order to gain success and peace. (6) The social-cultural value which is contained in the novel is related to the social-culture of the low to middle class of Javanese society.